Level of Serum Complements and Immunoglobulins in Iraqi Insulin Dependent Diabetes Mellitus - Hussein, H. K. Abdul; Asa, d, S. S.; Farid, Y. Y. Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Background: Diabetes mellitus (DM) accompanied with an increase in the death rate and represents a significant public health challenge. It is the cause of other disorders and infection in many body organs. Hence, it is important to study the possible changes in the immunological components in the serum of diabetic patients which are not well understood. In this work, serum C3, C4, IgA, IgG, and IgM were estimated in the patients with insulin dependent diabetes mellitus (IDDM) and compared with healthy persons. Patients and Methods: Twenty-one insulin dependent diabetic patients in addition to twenty-four healthy persons as control group were participated in this study. Serum C3, C4, IgA, IgG, and IgM were measured by using immunodiffusion plates. Results: The results showed a significant increase (p<0.05) in serum C3 and IgA while there is no significant difference (p>0.05) in the concentration of the complement C4 and serum IgG and IgM in IDDM patients as compared with healthy control group. Conclusion: The changes profile of some serum immunological components in IDDM can be explained in the means of the possible changes in immunity system as an inflammatory response in DM as a consequence of hyperglycemia. Comprehensive immunological study of all immunological changes in the IDDM patients is required for a complete explanation